German Economy Summer 2015 - German economy: Expansion rate remains high - Jens Boysen-Hogrefe; Salomon Fiedler; Dominik Groll; Nils Jannsen; Stefan Kooths; Galina Potjagailo (Kiel Institute for the World Economy (IfW), 2015)
The German economy remains on a robust growth track. For the current year we expect GDP to increase by 1.8 percent. Next year, the rate of expansion is likely to accelerate to 2.1 percent. The private consumption boom continues, albeit not quite at the same rapid pace as in the past quarters, as temporary stimulating factors are gradually subsiding. Investment spending is gaining strength and is to become the key economic driver next year, also against an ongoing favorable monetary backdrop. Exports are performing well in spite of an ongoing, difficult international environment and are additionally being stimulated by the euro depreciation. At the same time, imports are likely to accelerate substantially owing to the high economic momentum prevailing in Germany. Inflation is picking up again after a marked interim dampening by the oil price decline and will probably reach just under 2 percent next year. Employment trends continue to point upwards. At the same time, there are first signs of negative employment effects of the introduction of the legal minimum wage. Public-sector budgets continue to generate surpluses; this, however, is essentially a reflection of positive economic trends and not of any particular fiscal consolidation efforts. On the whole, there is a danger of economic policymakers misguidedly perceiving the positive cyclical development as an occasion for a respite. Considerable risks to the forecast remain (in particular from the external sector). However, the cyclical downside risks that would emerge from a further escalation of the crisis surrounding Greece are probably significantly lower than only a few years ago. – – Die Konjunktur in Deutschland ist weiter aufwärtsgerichtet. Für das laufende Jahr rechnen wir mit einem Anstieg des Bruttoinlandsprodukts von 1,8 Prozent. Im kommenden Jahr dürfte sich das Expansionstempo auf 2,1 Prozent beschleunigen. Der private Konsum boomt weiterhin, auch wenn er nicht mehr ganz so rasch zulegen wird wie in den vergangenen Quartalen, da temporär stimulierende Faktoren allmählich entfallen. Der Investitionsaufschwung festigt sich zusehends und wird im kommenden Jahr, auch vor dem Hintergrund der anhaltend günstigen monetären Rahmenbedingungen, voraussichtlich sogar zur wichtigsten Triebkraft der Konjunktur werden. Die Ausfuhren behaupten sich in einem nach wie vor iternational schwierigen Umfeld und werden durch die Abwertung des Euro zusätzlich stimuliert. Gleichzeitig dürften die Einfuhren aufgrund der hohen konjunkturellen Dynamik in Deutschland in deutlich beschleunigtem Tempo zulegen. Die Inflation zieht wieder an, nachdem sie zwischenzeitlich durch den Ölpreisverfall spürbar gedämpft worden war, und wird im kommenden Jahr wohl bei knapp 2 Prozent liegen. Die Beschäftigung bleibt weiter aufwärts gerichtet, wenngleich es erste Anzeichen dafür gibt, dass die Einführung des Mindestlohns bereits zu Arbeitsplatzverlusten geführt hat. Die öffentlichen Haushalte erzielen weiterhin Überschüsse; dies ist allerdings vor allem Ausdruck der günstigen Konjunktur und nicht besonderer Konsolidierungsanstrengungen. Insgesamt besteht die Gefahr, dass die Wirtschaftspolitik die gute Konjunktur als Ruhekissen auffasst. Die Risiken, die sich (vor allem aus dem außenwirtschaftlichen Umfeld) für die Prognose ergeben, sind nach wie vor beträchtlich. Allerdings sind die konjunkturellen Abwärtsrisiken, die sich aus einer weiteren Verschärfung der Krise um Griechenland ergeben würden, wohl deutlich geringer als noch vor einigen Jahren.
Keywords: 330; business cycle forecast; stabilization policy; leading indicators; outlook